Diel dynamics and coupling of heterotrophic prokaryotes and dissolved organic matter in epipelagic and mesopelagic waters of the central Red Sea. (10th September 2018) - García, Francisca C.; Calleja, Maria L.; Al‐Otaibi, Najwa; Røstad, Anders; Morán, Xosé Anxelu G.
Summary: The ecological status of an ecosystem can be approached by the taxa present but also by the size of individual organisms. In aquatic ecosystems, flow cytometry (FC) allows to study the individual size spectra and broad community composition through the evaluation of cytometric categories. The Red Sea represents a warm oligotrophic environment with a strong diel signal of vertically migrating mesopelagic fish, which feed at night at the surface and release dissolved organic carbon (DOC) at depth during day‐time. However, knowledge about how these conditions affect the dynamics of heterotrophic prokaryotes (HP) and their coupling with DOC is lacking. Here, we analyzed a high frequency sampling over 24 h to identify the community structure and compositional changes of HP in the epipelagic and mesopelagic layers of the central Red Sea. Our results show marked vertical and diel changes in HP communities in both layers. Specifically, the relative contribution of high nucleic acid content cells was remarkably linked to changes in DOC concentration and properties. The patterns observed were likely associated to the diel vertical migration of mesopelagic fish. These findings reveal that the structure of microbial communities in warm oligotrophic environments may be more dynamic than previously thought.